Retinal vascular geometry and its association to silent brain infarction - Jing Wang; Tingli Chen; Jing Wang; Xiyun Bian; Xiaowei Zhang; Xiaolong Yang; Xing Qi; Yihan Li; Haixia Huang; Qian Qian; Fei Yuan (BMC Ophthalmology)
Abstract Objective To examine the relationship between retinal vascular geometry and silent brain infarction (SBI) in the Chinese population. Methods We conducted a cross-sectional study that retrospectively analyzed the fundus photographs, MRI and other clinical data of 227 SBIs and 227 controls who visited Shanghai Health And Medical Center for physical examination. The retinal vessel fractal dimension (FD), retinal artery fractal dimension (FDa), retinal vein fractal dimension (FDv), central retinal artery diameter in the region from 0.5 ~ 1.0 disc diameter (DD) from the disc margin (CRAEB), central retinal artery diameter in the region from 1.0 ~ 2.0 DD from the disc margin (CRAEC), central retinal vein diameter in the region from 0.5 ~ 1.0 DD from the disc margin (CRVEB), central retinal vein diameter in the region from 1.0 ~ 2.0 DD from the disc margin (CRVEC), retinal arteriovenous diameter ratio in the region from 0.5 ~ 1.0 DD from the disc margin (AVRB), and retinal arteriovenous diameter ratio in the region from 1.0 ~ 2.0 DD from the disc margin (AVRC) were accessed by the Singapore “I” Vessel Assessment (SIVA) software. Results FD, FDa, FDv, CRAEB, CRAEC, CRVEB, CRVEC and AVRB in SBI subjects were 1.25 (1.21–1.28), 1.11 (1.08–1.14), 1.09 (1.06–1.13), 168.78 ± 19.39, 163.55 ± 18.97, 235.77 (222.64-254.08), 224.39 ± 23.29, 0.72 ± 0.06, respectively, significantly lower than those of control subjects [1.30 (1.28–1.32), 1.15 (1.13–1.18), 1.14 (1.12–1.16), 196.81 ± 27.94, 183.81 ± 25.46, 273.03 (247.59–296.30), 249.59 ± 32.03, and 0.73 ± 0.08]. Logistic regression results showed that higher FD (OR, 0.04), FDa (OR, 0.07), FDv (OR, 0.06), CRAEB (OR, 0.02), CRAEC (OR, 0.04), CRVEB (OR, 0.03), CRVEC (OR, 0.06), and AVRB (OR, 0.55) were associated with a lower of SBI. There was no significant difference in AVRC between the two groups. Conclusion Our study shows the association between retinal vascular geometry and SBI, and the results may provide new biomarkers for the early detection of SBI.